Insights Into Exhumation and Mantle Hydration Processes at the Deep Galicia Margin From a 3D High‐Resolution Seismic Velocity Model. Issue 7 (9th July 2022) - Boddupalli, Bhargav; Minshull, Tim A.; Bayrakci, Gaye; Lymer, Gaёl; Klaeschen, Dirk; Reston, Tim J.
Abstract: High‐resolution velocity models developed using full‐waveform inversion (FWI) can image fine details of the nature and structure of the subsurface. Using a 3D FWI velocity model of hyper‐thinned crust at the Deep Galicia Margin (DGM) west of Iberia, we constrain the nature of the crust at this margin by comparing its velocity structure with those in other similar tectonic settings. Velocities representative of both the upper and lower continental crust are present, but there is no clear evidence for distinct upper and lower crustal layers within the hyper‐thinned crust. Our velocity model supports exhumation of the lower crust under the footwalls of fault blocks to accommodate the extension. We used our model to generate a serpentinization map for the uppermost mantle at the DGM, at a depth of 100 ms (∼340 m) below the S‐reflector, a low‐angle detachment that marks the base of the crust at this margin. We find a good alignment between serpentinized areas and the overlying major block bounding faults on our map, suggesting that those faults played an important role in transporting water to the upper mantle. Further, we observe a weak correlation between fault heaves and serpentinization beneath the hanging‐wall blocks, indicating that serpentinization was controlled by complex faulting during rifting. A good match between topographic highs of the S and local highly serpentinized areas of the mantle suggests that the morphology of the S was affected by the volume‐increasing process of serpentinization and deformation of the overlying crust. Plain Language Summary: Continental rifting that occurred west of Iberia stretched and thinned the crust to less than 5 km thickness in the Deep Galicia Margin (DGM). We studied the nature of the thinned crust and upper mantle using seismic properties (P‐wave velocities). Seismic velocities indicate that the thinned crust includes both upper and lower crust rocks. Velocities also suggest that the lower crustal rocks were exhumed along faults that cut through the entire crust to accommodate the stretching during the extension. Using seismic velocities, we generated a map showing the upper mantle hydration patterns below the thinned crust. The map shows a good alignment between the tips of the major crustal faults that reach the mantle and the mantle hydration pattern, suggesting that faults transported water to the mantle. Further, we find a weak correlation between fault heaves and serpentinization, suggesting that the hydration process is controlled by complex faulting during rifting. Our map indicates that the surface of the crust‐mantle boundary (the S‐reflector) was affected by the hydration process that caused volume expansion of the mantle rocks and also by the deformation of the crust that locally pulled up the mantle rocks. Key Points: Exhumation of the lower crust under the footwall of the normal faults to accommodate extension Overlying faults in the crust control water transport to the mantle Topography of the S‐reflector is affected by the serpentinization process and deformations of the overlying crust